Optimal Life‐cycle Capital Taxation under Self‐control Problems. (8th August 2016) - Pavoni, Nicola; Yazici, Hakki
Abstract : We study optimal taxation of savings in an economy where agents face self‐control problems and the severity of these problems possibly depends on age. Focusing on quasi‐hyperbolic discounting, we show that if agents' ability to self‐control increases concavely with age, then savings should be subsidised and the subsidy should decrease with age. Quantitatively, we find that the optimal subsidies in our calibrated model with age‐dependent self‐control are much larger than those implied by models with constant self‐control. Our optimal subsidies are of comparable magnitudes to those implied by the 401(k) plan, even though the latter prescribes subsidies increasing with age.